The Urgency of Islamic Education Value in Social Studies Instruction at Madrasah Tsanawiyah Muhammadiyah Bandung - Ibnu Hurri; Hamidi Rasyid; Gandung Wirawan; Ernandia Pandikar (JETL (Journal of Education, Teaching and Learning), 2023)
This study intends to determine the significance of Islamic values education in social studies education in order to equip children from an early age with noble character (akhlaqul karimah). This is reflected in the Vision and Mission of Madrasah Tsanawiyah Muhammadiyah Bandung, as well as its curriculum and bylaws. The education of Islamic values in social studies learning at Madrasah Tsanawiyah Muhammadiyah Bandung is achieved through holistic social studies learning patterns, emphasizing the existence of social studies learning as general knowledge, and focusing on students' Islamic values in order to achieve learning goals. The research method used is qualitative research with a descriptive research design that outlines the conclusions of this study, namely the significance of incorporating the Islamic faith into social studies education. Data collection uses observation, documentation, interviews, and data analysis techniques using source and time triangulation. The results of this study are that Islamic values education has been carried out from an early age in Madrasah Tsanawiyah Muhammadiyah Bandung, both in the school environment and in the social studies learning process in the classroom, so that the link between general knowledge and Islamic values can be identified in achieving social goals. learn the purpose of learning, namely to produce good citizenship. Besides that, it can also bring up an understanding in students about positive values and avoid negative values.